Fluctuations in Stress Over Time During the First Year of Health Science Programs. - Rizzolo, Denise; Massey, Scott (Journal of Allied Health, 2020)
PURPOSE: Psychological adjustment can impact individuals at various points during the formative years of their educational process. Health science programs can be highly stressful and potentially negatively impact physical and psychological health. This study intended to explore the fluctuations in stress levels in health science students during their first year of graduate school. METHODS: Study participants included students enrolled in four graduate health sciences programs: Doctor of Physical Therapy (DPT), Occupational Therapy (OT), Speech-Language Pathology (SLP), and Physician Assistant (PA). Students completed the Brief Symptom Inventory (BSI) during the first week of graduate school (time 1), during the last 2 weeks of semester 1 (time 2), and at mid-semester for semester 2 (time 3). Subscales on the BSI included anxiety, depression, obsessive compulsive, phobia and somatization. RESULTS: A total of 79 students completed the scale at all three time points. Mean anxiety scores changed over time from time 53 at time 1, 57 at time 2, to 54 at time 3. At the three time points, mean depression scores were 53, 56, and 53; mean obsessive-compulsive scores were 57, 63, 59; mean phobia scores 51, 50, and 50; and mean somatization scores 49, 54, and 51. DISCUSSION: There are notable fluctuations in anxiety levels in health science students, and therefore, it is necessary to assist students in developing effective stress management techniques to help moderate the negative consequences of stress.